TECHNOLOGY ACCEPTANCE MODEL FOR BUILDING INFORMATION MODELLING BASED VIRTUAL REALITY (BIM-VR) IN COST ESTIMATION - Minghui, Lee; Chai, Changsaar; Xiong, Yaoli; Gui, Hun Chuen (International Council for Research and Innovation in Building and Construction , Netherlands, 2022)
The accuracy of cost estimation during the preliminary stage of a construction project is imperative. However, owing to limited accessibility of information, the level of accuracy required at this stage of a project is extremely difficult to be attained. In like manner, the risks of budget shortages or cost overruns are likely to surge exponentially due to an incompetent or a lackadaisical approach towards life-cycle costing. Hence, this study proposes BIM-based VR as a preliminary estimating solution which is purported to nip the aforementioned issues in the bud. BIM-VR enables BQ to be updated automatically as stakeholders performs modifications on-the-go, allowing speedy and highly accurate design adjustments throughout the project. On this front, the Technology Acceptance Model (TAM) was adopted to determine the acceptance level of BIM-based VR technology in Malaysia. Data was acquired via a questionnaire survey, of which 92 out of 180 distributions were accepted for analysis, accounting to a respectable response rate of 51%. Consequentially, Principal Component Analysis result revealed that ‘Saving Cost and Resources’ is the most significant factor for BIM acceptance. Conversely, ‘Presence of Skill Gap’ was found to be the biggest stumbling block for BIM-based VR in cost estimation. Relationship analysis from the TAM also unveiled that the challenges of BIM-based VR did not produce mediating effect towards attitude and intention to use. This implies that the intention of construction professionals to adopt the technology wasn’t impeded by its challenges. Significantly, this study served as a benchmark in uncovering new possibilities of BIM and VR in project cost management, where the reliability and accuracy of conventional procurement can be enhanced with technology, particularly in BQ documentation, to fulfill the rising expectations of construction stakeholders across the globe.